TRANSCRANIAL DIRECT CURRENT STIMULATION AND AUGMENTATIVE AND ALTERNATIVE COMMUNICATION FOR CHILDREN WITH CEREBRAL PALSY: RANDOMIZED CONTROLLED DOUBLE-BLIND CLINICAL TRIAL - Ramos, Amanda Macedo de Freitas Souza; Silva, Paula Soares da; Silva, Sara Viana de Abreu; Oliveira, Caroline Priscila de; Silva, Rafael dos Anjos; Ferreira, Giselle Araujo; Silva, Marcele Paganoto Garcia Rodrigues da; Araújo, Marcela de Oliveira; Collange, Luanda André (CIPEEX, 2025)
The objective of the research project is to compare the effects of ten sessions of speech therapy intervention with Augmentative and Alternative Communication (AAC) during the use of transcranial direct current stimulation (tDCS) on the active and placebo dorsolateral prefrontal cortex in the Activity and Participation domain of the ICF for children with CP. It is a randomized, placebo-controlled, double-blind clinical trial involving 24 children diagnosed with CP, aged between 6 and 12 years. The participants will be evaluated one week before, one week, and one month after the intervention, through the application of the Communication Matrix, Pediatric Assessment Inventory of Dysfunction, and Participation and Environment Measure for Children and Youth. The experimental group will undergo speech therapy intervention with AAC associated with the application of active anodal tDCS over the left dorsolateral prefrontal cortex. The control group will undergo speech therapy intervention with CAA associated with placebo tDCS. The intervention will involve ten intervention sessions, carried out over two consecutive weeks and lasting 20 minutes each. Considering the potential effect of anodal tDCS on the left dorsolateral prefrontal cortex, it is expected that the intervention will enhance the effect size of the speech therapy intervention with AAC in children with CP.